A Study into the Implementation of the Public Private Partnership (PPP) Policy in Ghana- Case Study Obuasi Municipal Assembly, Ashanti Region. - Amprofi, Tawiah David (2017)
A Thesis submitted to the Department of Building Technology, College of Art and Built Environment in partial fulfilment of the requirements for the degree of Master of Science,